A Blockchain-Assisted Cross-Domain Authentication and Key Negotiation Scheme in IIoT - Zhengnan Xu; Guofang Dong; Ruicheng Yang (IEEE Access)
Traditional cross-domain schemes for industrial Internet of Things (IIoT) are deficient in decentralization and lack a precise mechanism for updating session keys, resulting in high overhead from repeated authentication and key negotiation. This paper proposes a blockchain-assisted cross-domain authentication and key negotiation scheme, aiming at realizing authentication and key negotiation between different domains of IIoT. First, a session token mechanism is introduced to limit the validity period of the negotiated session key and assist in updating the session key. Second, blockchain is utilized to assist in updating the validity period of the session key, thus significantly reducing the overhead of repeated authentication. Finally, we analyze the security and performance of the scheme, and the results show that the scheme can efficiently verify data integrity and add the functions of key update, user dynamic update, and semi-trusted third-party dynamic update. The experimental results show that compared with other schemes, our scheme reduces 69.4%, 78.9%, 88.8%, and 38.3% of the time consumed in terms of computation overhead and reduces 63.5%, 18.8%, 15.1%, and 52.9% of the cost in terms of communication overhead, respectively. The proposed scheme has a low overhead.